Kecanduan Game Online sebagai Gejala Nekrofilia Sosial: Analisis Humanistik Erich Fromm dalam Masyarakat Digital - Sudarso, Yosep; Boymau, Yerliani; Seo, Marwela R.; Djawa, Maya (Widyadewata, 2025)
This article explores the phenomenon of online game addiction in digital society through the lens of Erich Fromm’s theory of necrophilia. Fromm interprets necrophilia not merely as a sexual disorder but as a personality orientation that favors the dead, static, and mechanical. Employing a descriptive qualitative approach with a humanistic analysis, this study investigates how game addiction reflects social necrophilic symptoms and affects interpersonal relationships and psychosocial life. Findings indicate that game addiction is not only a behavioral issue but a sign of modern human alienation from authentic and living relationships. Fromm proposes biophilia—a love of life—as a counterpoint, highlighting the importance of human connection, empathy, and life values. The study recommends value-based education and the development of a healthy digital culture as both preventive and curative strategies against game addiction. Keywords:Social nekriphilia, Game Addiction, Erivh Fromm, Digital Society